SENTENCE PARTS - Aralova Matluba Qodir qizi; Akhrorova Mahina (International Journal of Literature and Language Studies, 2026)
Abstract. This article analyzes the ways of developing students’ communicative competence in the process of teaching sentence parts in 8th-grade mother tongue lessons at general secondary schools. The study reveals that limiting grammatical knowledge only to theoretical analysis does not sufficiently stimulate students’ speech activity. Based on the communicative approach, interactive methods such as “Fishbone,” “Problem Situation,” “Charxpalak,” and “Find Your Friend” were applied in the lesson process. Through these methods, positive changes were observed in students’ skills of identifying sentence parts, analyzing them based on meaning, and consciously using them in oral and written speech. The obtained results show that teaching sentence parts on a communicative basis contributes to improving students’ speech culture and readiness for communication.